2010
DOI: 10.1097/cmr.0b013e3283390696
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of stable cell lines for personalized melanoma cell vaccine

Abstract: Personalized vaccine, recognized after the failure of allogenic melanoma whole cell and lysate vaccine phase III trials, involves culturing cells from a patient's own tumor within a short duration and with less passages but with optimized expression of tumor-associated antigens (TAAs). Its feasibility is established by comparing pure cell lines generated from fresh and cryopreserved tissues (n=164) of patients with lymph node (LN) and distant metastases. Stable cell lines (from 67% of specimens) are subculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Autologous melanoma cell lines were generated separately from TILs either from tumor fragments or from a combination of cells recovered from suspension in transport medium or after mincing, as previously described (16,18).…”
Section: Generation Of Tils and Melanoma Cell Linesmentioning
confidence: 99%
“…Autologous melanoma cell lines were generated separately from TILs either from tumor fragments or from a combination of cells recovered from suspension in transport medium or after mincing, as previously described (16,18).…”
Section: Generation Of Tils and Melanoma Cell Linesmentioning
confidence: 99%
“…Cell line authentication was carried out by an STR identifier kit (Applied Biosystems) and both cell lines used in the study showed at least a 90% match to the STR profiles of ESTDAB (Supplementary Table S1). The early-passage GEWA and KADA melanoma cell lines were established from patients at the oncology clinic at Karolinska University Hospital (ethical permit: #2011/143-32/1) based on the published protocol (25). Mycoplasma-free (MycoAlert kit) GEWA and KADA cell lines were in their 7 th and 6 th passage when used for tumormonocyte coculture, respectively.…”
Section: Tumor Coculture and Mdsc Isolationmentioning
confidence: 99%
“…25 Generation of a DC vaccine employing purified autologous tumor cells as the antigen source has been shown to be feasible and perhaps preferable by virtue of containing a patient-specific repertoire of tumor-associated antigens. 18,26 The difficulty and expense of generating purified autologous cell lines may be outweighed by the benefits of having the full complement of tumor-associated antigens in the patient-specific product. Some clinical trials are using unpurified autologous bulk tumors with some success; however, it is not known whether contaminating fibroblasts and/or necrotic tissue affect the immunotherapeutic product.…”
Section: Discussionmentioning
confidence: 99%
“…Pure tumor cells generated and characterized as previously reported [16][17][18] were expanded to 200 million cells and then incubated with 1000 IU/mL of IFN-c (InterMune) for 72 hours in 15% FBS/ECS in RPMI (complete medium), irradiated with 100 Gy from a cesium source, and cryopreserved as previously described. 19 The IFN-c-treated and irradiated tumor cells were recovered from cryopreservation, washed 3 · with PBS, and then added to the in vitro cultivated DCs and incubated for *24 hours.…”
Section: Autologous Tumor Cell Line Generationmentioning
confidence: 99%